Degree of Convergence of a Function in Generalized Zygmund Norm Using Karamata-Matrix (KλA) Product operator (European Journal of Pure and Applied Mathematics, 2023)
In the present paper, we obtain the results on the degree of convergence of a function of Fourier series in generalized Zygmund space using Karamata-Matrix (KλA) product operator. We also study an application of our main result.
Keywords: Degree of convergence; generalized Zygmund space; Karamata- Matrix transformation; Fourier series; modulus of continuity